THE CORRELATION OF PSYCHOLOGICAL COUNSELING IN PKPR WITH THE ABILITY TO PROBLEM SOLVING ADOLESCENTS AGED 13-15 YEARS AT LOWER SECONDARY SCHOOL STATE 1 PURI MOJOKERTO - binarti dwi wahyuningsih; lutfi wahyuni wahyuni (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2018)
THE CORRELATION OF PSYCHOLOGICAL COUNSELING IN PKPR WITH THE ABILITY TO PROBLEM SOLVING ADOLESCENTS AGED 13-15 YEARS AT LOWER SECONDARY SCHOOL STATE 1 PURI MOJOKERTO By: Binarti Dwi,Lutfi Wahyuni, Abctract : This study aims to analyze correlation between the role of adolescence care services (PKPR) particular program as psychological counseling to problem solving capabilities in adolescent aged 13-15 years at lower secondary school state 1 puri Mojokerto. This study used is analytic with cross-sectional. A simple of 52 people were taken by cluster random sampling. Protap monitoring data collection using standard PKPR 3 adolescence, especcially psychological counseling program and questionnaire problem solving abilities. Spearman rho test showed that p (0,000) < Î± (0,05) so, H0 is rejected it means there is correlation of psychological counseling in pkpr with the ability to problem solving adolescents aged 13-15 years at lower secondary school state 1 puri Mojokerto. Whith valve r-0,474 which shows correlation moderat. To improve quality of Psychological counseling services in PKPR expected to help adolescent choose alternative solotions to problems and improve the ability of problem solving in adolescent.